The given expression is
![6y-(2y-5)=29](https://img.qammunity.org/2023/formulas/mathematics/college/sjx47ydh0s5hmj5z1tpb7kadw8tdb4cdv0.png)
First, we use the distributive property to solve the parenthesis, we have to multiply the negative sign with each term inside the parenthesis.
![6y-2y+5=29](https://img.qammunity.org/2023/formulas/mathematics/college/dy972lj58pv3q06l1jc1bnzi7fknf2tnck.png)
We reduce like terms, 6y and -2y are like terms in this case,
![4y+5=29](https://img.qammunity.org/2023/formulas/mathematics/college/911as7tcb1xvqrtg0hfmn6j6cw9pfbwfoh.png)
Then, we subtract 5 on each side.
![\begin{gathered} 4y+5-5=29-5 \\ 4y=24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lt89bcu143o55gq7batcw6pe857th05cfg.png)
At last, we divide the equation by 4.
![\begin{gathered} (4y)/(4)=(24)/(4) \\ y=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3zyi6ybkedd7tvxplpavhsji3i25l20gph.png)
Therefore, the solution is 6.